Natural Occurrence and Analysis of Nosema sp. Infection in the Adult Population of Western Bean Cutworm in Michigan. Issue 1 (5th December 2022) - Bunn, Dakota C; Miller, Nicholas
Abstract: An understanding of population dynamics and insect biology is important for effective crop management strategies. Biotic factors such as pathogens play a large role on the fitness and dynamics of insect populations. Microsporidia are obligate intracellular parasites that infect more than 150 insect species and range from sublethal and chronic to fast acting and deadly. The western bean cutworm, Striacosta albicosta (Smith) (Lepidoptera: Noctuidae), is a pest of both corn ( Zea maize L. [Poales: Poaceae]) and dry beans ( Phaseolus sp L. [Fabales: Fabaceae]) that is infected by a microsporidian parasite from the genus Nosema (Microsporidia: Nosematidae). Unfortunately, little is known about the interactions between the Nosema sp. (Microsporidia: Nosematidae) infecting the western bean cutworm and its prevalence and effects on the host population. This is especially true for the western bean cutworm population that has settled in the Great Lakes region over the last two decades. Using field caught samples and phase contrast microscopy, no consistent trends in pathogen load were observed over the course of the western bean cutworm flight season. A weak, but statistically significant relationship was observed between male body weight and pathogen load. Overall, we found a 100% prevalence of infection in the adult western bean cutworm population in Michigan.